Features of CDH1, CTNNB1 genes transcriptional activity and expression levels of E-cadherin, β-catenin proteins coded by these genes on the I, II, III, IV stages of colorectal adenocarcinoma development - M. A. Shyshkin; V. O. Tumanskyi (Patologìâ)
Aim – analysis of CDH1 and CTNNB1 genes mRNA expression levels and expression levels of E-cadherin, β-catenin proteins coded by these genes, and also their correlations with KRAS gene transcriptional activity level on the I, II, III, IV stages (pTNM) of colorectal adenocarcinoma (CRA) development.